Synthesis and investigation of structural, magnetic and dielectric properties of zinc substituted cobalt ferrites. (December 2018) - Atif, M.; Asghar, M.W.; Nadeem, M.; Khalid, W.; Ali, Z.; Badshah, S.
Abstract: A series of zinc substituted cobalt ferrite samples i.e., Co1-x Znx Fe2 O4 ( x  = 0.0–0.6) were synthesized by sol-gel method. X-ray diffraction patterns confirmed the formation of pure-phase cubic spinel structure in the prepared samples. Cation distribution between the tetrahedral and octahedral sites were estimated by refining the XRD patterns by Rietveld method. Magnetic studies revealed that the saturation magnetization is maximum for x  = 0.4 sample; whereas the values of coercivity, magnetic anisotropy constant and magnetostriction decreased with increasing x . However, a considerable enhancement in the magnitude of strain sensitivity is obtained for x  = 0.4 sample in comparison to other substituted samples. The observed variations in the magnetic results are discussed on the basis of site occupancies of the cations and decreased anisotropy of the prepared samples whereas the microstructure plays insignificant role. Moreover, the dielectric measurements indicated a reasonable value of dielectric constant at low frequencies along with a low value of ac conductivity for x  = 0.4 sample due to electron–hole compensation at octahedral sites of the spinel structure. Here, it is suggested that x  = 0.4 composition exhibits the optimal magnetic and dielectric properties in the Co1-x Znx Fe2 O4 system that could make this composition as a potential candidate for stress sensor applications. Graphical abstract: Image 1 Highlights: Phase pure synthesis of zinc substituted cobalt ferrites by sol-gel. Substitution of non-magnetic Zn 2+ ions strongly influences the properties of cobalt ferrites. The variations in physical properties are attributed to cation distribution and reduced anisotropy of the system. Maximum M s, moderate ε / with low σac and enhanced dλ/dH for x  = 0.4 sample suggests its potential in sensing devices.